2004
DOI: 10.1097/00001756-200401190-00001
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of bone marrow stromal cells into the cochlea of chinchillas

Abstract: This study aimed to evaluate the potential of bone marrow stromal cells for treatment of inner ear diseases. Autologous marrow cells labeled with Dil were implanted into the inner ear of five gentamicin-treated chinchillas. Histological analysis 3 weeks later revealed robust survival of grafted marrow cells in multiple regions within the cochlea. Marrow cells implanted in the basal turn of the cochlea migrated as far as the apical end or into the spiral ligament of the cochlea. Some grafted cells expressed a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
67
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 14 publications
2
67
0
2
Order By: Relevance
“…Previous studies have reported that transplanted stem cells survived within the cochlear environment for periods of 3-4 weeks, and that the transplanted cells migrated throughout all turns of the cochlea [99][100][101], into the modiolus [100,102,103], and to the vestibular organs [64,104]. While the spread of stem cells may be beneficial in terms of replacing lost or damaged SGNs and/or hair cells within the cochlea, it would not be desirable for the cells to spread beyond the cochlea.…”
Section: Delivery Techniques For Neurotrophin Administration In the Cmentioning
confidence: 99%
“…Previous studies have reported that transplanted stem cells survived within the cochlear environment for periods of 3-4 weeks, and that the transplanted cells migrated throughout all turns of the cochlea [99][100][101], into the modiolus [100,102,103], and to the vestibular organs [64,104]. While the spread of stem cells may be beneficial in terms of replacing lost or damaged SGNs and/or hair cells within the cochlea, it would not be desirable for the cells to spread beyond the cochlea.…”
Section: Delivery Techniques For Neurotrophin Administration In the Cmentioning
confidence: 99%
“…The survival of autologous BMSCs grafted in the cochlea was proven [26,28,40]. The enhanced survival of BMSCs was confirmed in deafened cochleae [26]. Autologous BMSC-derived neurospheres transplanted into the cochlear modiolus of the deafened guinea pigs settled predominantly in the internal acoustic meatus [28].…”
Section: Regeneration Of Spiral Ganglion Neuronsmentioning
confidence: 91%
“…We review previous reports and discuss obstacles to overcome for successful functional recovery. Several kinds of pluripotent stem cells have been delivered into the cochlea for the regeneration of SGNs, including NSCs [10,13,46], ESCs [4,5,11,12,29,34,36,38], bone marrow stem cells (BMSCs) [26,28,40], and iPSCs [27]. Tamura et al, evaluated the ability of NSCs to achieve neural differentiation in the modiolus of the cochlea and demonstrated that some grafted NSCs expressed β-III tubulin, a neuronal marker, although the majority of them differentiated into glial cells [46].…”
Section: Regeneration Of Spiral Ganglion Neuronsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fate of autologous BMSCs after intra cochlear transplantation was also investigated. Autologous BMSCs in the cochlea were observed to differentiate to neurons 12 . In addition, the transplanted BMSCs migrate to different parts of the cochlea.…”
mentioning
confidence: 99%